Nos habíamos terruqueado tanto: cómo y por qué el poder instrumentaliza el concepto “terrorismo” - Jordán, Rubén (Pontificia Universidad Católica del Perú, 2024)
This paper examines the discursive appropriation of the concept of “terrorism” by the contemporary establishment. Drawing some indications from the political philosophies of Plato and Hobbes, who share a similar enthusiasm for violence as an instrument of power, the argument is made that the misuse of the concept of “terrorism” functions as a mechanism for the self-legitimation and self-affirmation of power. This is the case because power, through widely disseminated doctrinal systems, presents terrorist acts as a sample of the hypothetical state of total chaos that would arise if its current configuration were modified.

El presente artículo explora la apropiación discursiva que el poder contemporáneo hace del concepto “terrorismo”. A partir de algunas indicaciones de las filosofías políticas de Platón y de Hobbes, similares en cuanto a su encomio de la violencia como herramienta del poder, se defiende que abusar del concepto “terrorismo” sirve al poder como mecanismo de autolegitimación y autoafirmación. Esto es así porque el poder, a través de sistemas doctrinales muy diseminados, presenta los actos terroristas como una muestra del hipotético estado de caos total que surgiría si se modificara su actual configuración.
Keywords: Terrorism; Terrorist-dubbing; Power; Violence; Propaganda; Terrorismo; Terruqueo; Poder; Violencia; Propaganda; https://purl.org/pe-repo/ocde/ford#6.03.01